Choledochoduodenal fistula: A rare cause of upper gastrointestinal bleeding in a child - Gülcü Taşkın, Didem; Beser, Faruk; Adaletli, İbrahim; Cullu, Fugen; Kutlu, Tufan; Erkan, Tulay (Journal of Surgery and Medicine, 2022)
Spontaneous choledochoduodenal fistula (CDF) is a rare form of biliary enteric fistula. A child with CDF who had a motor vehicle collision as a pedestrian at the age of 2 years is presented in this article. Since the accident, recurrent abdominal pain and black-colored stools were noted thrice a year. As a 13- year-old, the patient was admitted with vomiting of blood and melena. He was hospitalized with gastrointestinal bleeding. Endoscopy is performed because of bleeding and a fistula was detected incidentally. Barium swallow series and magnetic resonance cholangiopancreatography showed a fistula tract. Endoscopic retrograde cholangiopancreatography (ERCP) confirmed the definitive diagnosis and guided treatment. In our case, we emphasize the importance of ERCP in facilitating the diagnosis of CDF. Barium swallow radiography detects the passage of barium to the biliary system in only half of the CDF patients diagnosed via ERCP. In summary, we reported the youngest case of CDF with a large fistula orifice managed by endoscopic sphincterotomy.